Emission and transformation behavior of minerals and hazardous trace elements (HTEs) during coal combustion in a circulating fluidized bed boiler. (November 2018) - Fu, Biao; Liu, Guijian; Sun, Mei; Hower, James C.; Mian, Md Manik; Wu, Dun; Wang, Ruwei; Hu, Guangqing
Abstract: Emission of hazardous trace elements (HTEs) from energy production is receiving much attention due to concerns about the toxicity to the ecosystem and human health. This study presented new field measurement data on the HTEs partitioning behavior and size-segregated elemental compositions of gaseous particular matter (PM) generated from a commercial circulating fluidized bed (CFB) power plant. Mineralogical and morphological characteristics of combustion ash and P M 2.5 (particle diameter less than 2.5 μm ) were determined by X-ray diffractometer (XRD) and scanning electron microscopy with energy dispersive X-ray spectroscopy (SEM/EDS). Functional groups alteration during CFB combustion was characterized by Fourier transform infrared spectroscopy (FTIR). The presence of aliphatic hydrogen at 2910 c m − 1 and 2847 c m − 1 in the P M 2.5 suggested that the aliphatic carbon-rich volatiles were absorbed on the fine particles with large surface area. Fine fly ash ( P M 2.5 ) occurred as irregular glass particles or/and as unburned carbon. The typical irregular particles were mainly composed of Al-Si-Ca or Al-Si-Fe phases. The enrichment behavior of HTEs was determined for the airborne size-segregated particular matter. Elemental occurrences, combustion temperature, unburnt carbon, and limestone additives during CFB combustion were critical in the transformation behavior of HTEs. The total potentially mobile pollutants that exit the CFB power plant every year were estimated as follows: 0.22 tons of Cr, 0.12 tons of Co, 0.73 tons of Ni, 0.04 tons of As, 0.07 tons of Se, 3.95 kg of Cd, and 3.34 kg of Sb. Graphical abstract: Image 1 Highlights: The mineralogical and morphological characteristics of combustion ash and PM 2.5 were investigated. The enrichment behavior of HTEs was determined for the airborne size-segregated particular matter. The transformation mechanisms of HTEs during CFB combustion were studied. The possible transfer of contaminants from combustion wastes to the local environment were evaluated. Abstract : Emission characteristics and migration behavior of minerals and HTEs during CFB combustion were demonstrated.